In-person versus online delivery of a behavioral sleep intervention (Sleeping Sound©) for children with ADHD: protocol for a parallel-group, non-inferiority, randomized controlled trial - Maya K. Malkani; Andrew M. C. Sheridan; Alison J. Crichton; Romola S. Bucks; Carmela F. Pestell (BMC, 2023)
Abstract Background Children with Attention-Deficit/Hyperactivity Disorder (ADHD) often experience sleep difficulties such as difficulty initiating and maintaining sleep. Problem sleep may impact children's daily functioning and behaviors and exacerbate ADHD symptoms. Most effective behavioral interventions to improve sleep are conducted in person, limiting accessibility to treatment for individuals in remote or rural communities or those who are unable to attend a clinic. This trial aims to assess the efficacy of delivering an established behavioral intervention online, Sleeping Sound with ADHD©, compared to a face-to-face delivery mode. Methods This parallel group, non-inferiority, randomized controlled trial (RCT) will include at least 68 children, aged 5-12 years old with ADHD. Families of children will be recruited from private developmental and psychological clinics and social media, within the state of Western Australia (WA). Once written informed consent and baseline questionnaires are completed, families are randomized to receive the behavioral intervention either in-person or online via Telehealth services. The intervention targets the assessment and management of reported sleep problems, through two individual consultations and a follow-up phone call with a trained clinician. The sleep outcomes assessed consist of a parent-reported sleep questionnaire and actigraphy. Discussion To the best of our knowledge, this is the first RCT to investigate sleep treatment modality for children with ADHD. If effective, clinicians can provide an evidence-based sleep intervention in an accessible manner. Trial registration ANZCTR, ACTRN12621001681842 . Registered 9 December 2021-Retrospectively registered.